OR49. Predictor of prolonged length of stay in patients hospitalized with acute coronary syndrome. (23rd November 2021) - Ardining, H; Amshar, M; Akbar, F; Ulfiarakhma, D; Nathania, M; Napu, R; Karimullah, M D H; Widyantoro, B
Abstract: Aims: Acute coronary syndrome (ACS) is responsible for high rates of hospital admission with high cost burden. Knowing patients with projected prolonged length of stay (LOS) could enable clinicians to do early interventions and better preparations. This study aims to identify factors associated with prolonged LOS in ACS patients at the time of admission. Method and Result: We included 237 ACS patients admitted to Kediri General Hospital and Bogor General Hospital between January and June 2020. Patients who died during hospitalization or discharged by their own will were excluded. Data were collected retrospectively and analyzed using SPSS v25. Prolonged LOS was defined as LOS more than 6 days. The mean age was 57.5±0.7 years, majority was male (65.8%) and had diagnosis of NSTE-ACS (56.5%). The median LOS was 5 days (2-23), and the prevalence of prolonged LOS was 18.1%. On bivariate analysis, factors associated with prolonged LOS were high risk age (men > 40 years and women > 50 years) (p = 0.01), hypotension (p < 0.01), decreased consciousness (p = 0.004), sign of shock (p = 0.002), tachycardia (p = 0.001), and higher Killip class (p = 0.002). After multivariable adjustment and stepwise elimination, hypotension was found to be significant independent predictor for prolonged LOS (OR 38.512 [95% CI 4.5-328], p = 0.001). The area under the receiver operating characteristic curve (AUC) was 0, 704 (95% CI 0.614-0.794) which showed acceptable discrimination, and calibration was good (Hosmer-Lemeshow test: p = 0.96). Conclusion: Hypotension was found to be strong independent predictor for prolonged LOS in ACS patients.